Pengaruh Literasi Keuangan, Pendapatan, dan Risiko Investasi Terhadap Keputusan Investasi Reksa Dana Generasi Z Yang Terdaftar di Kustodian Sentral Efek Indonesia (KSEI) - Agustriyanda, Ferry Elfin; Fathihani; Frimayasa, Agtovia (STKIP MAJENANG, 2025)
Generation Z in Indonesia is increasingly interested in investment, particularly in mutual funds, but still faces challenges such as low financial literacy and a lack of understanding of investment risks. This study aims to analyze the influence of financial literacy, income, and investment risk on mutual fund investment decisions among Generation Z registered with the Indonesian Central Securities Depository (KSEI). This research employs a quantitative descriptive method with a causal approach to examine the cause-and-effect relationship between independent variables (financial literacy, income, and investment risk) and the dependent variable (mutual fund investment decisions). The study population consists of Generation Z investors who invest through KSEI, with a sample of 100 respondents selected using a non-probability sampling technique, specifically purposive sampling. Data collection was conducted through questionnaires as the primary instrument, supplemented by secondary data from journals, books, and other sources. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 29. The research results show that financial literacy, income, and investment risk have a positive and significant influence on mutual fund investment decisions among Generation Z registered with the Kustodian Sentral Efek Indonesia (KSEI).